RESPON GURU TERHADAP PENGGUNAAN BUKU PANDUAN PENYUSUNAN LKS (LEMBAR KEGIATAN SISWA) BERBASIS MULTIPLE INTELLIGENCES - Dian Ika Kusumaningtyas; Maharani Putri Kumalasani (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2019)
This research was conducted with the aim to determine the extent of teacher responses related to the use of manuals for compiling LKS based on Multiple Intelligences. In this study using descriptive qualitative research. Data collection procedures carried out by observation, documentation, and questionnaires. While this study uses data analysis of the Miles and Huberman models. The results obtained from this study are the teacher gives a positive response related to the use of manuals for compiling LKS based on Multiple Intelligences. The teacher is more helpful or easier to understand LKS and types of intelligence. The teacher does not feel difficulties in making worksheets, because in the guide can provide inspiration to innovate in making worksheets.